PENGARUH JENIS BAHAN ATAP PADA PROSES DESALINASI EVAPORASI AIR LAUT - Novitrie, Nora Amelia; Afiuddin, Ahmad Erlan; Hardiansyah, Rizal (2477 - 6165, 2017)
Treatment technology of sea water into freshwater is known as desalination. An effective and economical desalination technique is desalination with evaporation. Thisstudy aims to determine the effect of roofing materials on the amount of freshwater produced. The study was conducted using a miniature evaporative tub that had a rooflike shape. Evaporative tubs dimension was 1m x 1m x 0.02m of laminated wood material. 20 liters of brackish water was pumped into the tub. Water in the tub was then closed using a roof designed like a roof made of fiberglass and polycarbonate. Brackish water was left in contact with the sunlight for 24 hours. As a result of heat transfer from sunlight to evaporation tub, brackish water experienced evaporation. The steam moved upward and was captured by the roof wall then condensated resulting in fresh water. The conclusion obtained was a miniature roof of evaporative desalination using fiberglass material obtained 427 ml of fresh water while using polycarbonate material obtained 136 ml fresh water. Keywords: Roof, Desalination, Evaporation.